A study of unorthodox town making by Akira Tamura: the transmission of Tamura’s vision to younger generations - Aoki, Atsuhiro (International Planning History Society Proceedings, 2018)
This thesis intends to assess how Akira Tamura’s “Town making” vision has been passed down to and utilised by younger generations, focusing on the experiences of a study group in which Tamura’s successors have utilised his vision. Tamura promoted the group as an informal place to convey and understand the essence of town making, and insisted on the importance of flexibility in consideration of stakeholders. This thesis sets out to answer the following questions: (1) what are the key features of Akira Tamura’s town making that have been passed on, and (2) how can they be applied by town planners now and in the future? In preparation for writing this thesis, I conducted semi-structured interviews of 4 former Yokohama public officials and referred to documents in the “Akira Tamura archives” of Yokohama city’s historical library. This case study demonstrates that Tamura aimed not only to improve the law and revise the planning system itself, but to imbue urban planning with greater fluidly.